The Effect of DMSO of Different Concentrations and Freeze-Thawing on Newborn Rat Neural Cell Survival - Lyashenko, T. D.; Sukach, A. N. (Problems of Cryobiology and Cryomedicine, 2024)
The effect of cryoprotectant dimethyl sulfoxide of different concentrations on the ability of isolated neural cells of newborn rats to proliferate and to be stained with trypan blue before and after freeze-thawing was studied. The cryoprotectant concentrations of 7.5 and 10% were established as the optimal ones, which preserved the ability of the neural stem/progenitor cells of newborn rats to proliferate and differentiate after freeze-thawing. Preservation of the functional activity of newborn rat neural cells demanded the presence of serum in freezing medium. It was demonstrated that the viability of newborn rat neural cells, assessed by trypan blue exclusion, only partially reflected the cell functional activity.